Sustainable Bauxite Mining Guidelines - Prosser, M.; Johnson, M.; Saptaji, Kushendarsyah (Penerbit Universiti Malaysia Pahang, 2017)
The demand for bauxite will be increased in the future due to the needs for aluminium products. The sustainable mining guidelines especially in bauxite mining industry is necessary to be implemented. The guidelines will help the mining company, environmental agency and government agency in addressing the sustainable issues related with the bauxite mining. This paper describes the development of the guidelines for sustainable bauxite mining by discussing the reasons why the guidelines must be developed and some key aspects that needed to be examined in order to have the sustainable bauxite mining.